Pest and Disease Control in Cavendish Banana Seedlings Resulting from Tissue Culture - Indah Sari Dwi Agustin; Penta Suryaminarsih; Putranto Sasikirono; Yenny Wuryandari (Future Science, 2021)
Cavendis banana cultivation can use tissue culture as one of the developments of cultivation in the era of disruption. However, the results of tissue culture are very susceptible to attack by nuisance organisms during acclimatization to plant culture. The control carried out against the attack of plant-disturbing organisms in addition to using fungicides and insecticides, also applies preventive control. The purpose of this study was to determine an effective and smart way to control pests and diseases in tissue cultured Cavendish banana seedlings. Preventive control of pests and diseases using the method of thinning the seeds and soaking the seeds with fungicides. Data analysis was carried out using descriptive and parametric data. This study was conducted using a completely randomized design (CRD) with four control treatments. Each treatment was repeated 4 times. The control treatments carried out consist of: Control (A), preventive control (B), chemical control (C), and a combination of preventive and chemical control (D). The results of the control carried out showed that the combination of preventive and chemical control treatments gave significant results in inhibiting the attack of pests and diseases of Cavendish banana seedlings from tissue culture.